Complications following primary and revision transsphenoidal surgeries for pituitary tumors. (27th September 2014) - Krings, James G.; Kallogjeri, Dorina; Wineland, Andre; Nepple, Kenneth G.; Piccirillo, Jay F.; Getz, Anne E.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis This study aimed to determine the incidence of major complications following both primary and revision transsphenoidal pituitary surgery. Major complications included endocrinopathic, skull base, orbital, hemorrhagic and thromboembolic complications, respiratory failure, and death. Secondarily, this study aimed to examine factors associated with the occurrence of complications. Study Design Retrospective cohort analysis of California and Florida all‐payer databases from 2005 to 2008. Methods The major complication rate following both primary and revision transsphenoidal pituitary surgery was calculated. Bivariate analyses were performed to investigate the relationship of patient characteristics with complication occurrence, and a multivariate model was constructed to determine risk factors associated with these complications. Results There were 5, 277 primary cases and 192 revision cases that met inclusion criteria. There was a nonsignificant absolute difference of 3.09% (95% confidence interval [CI]: −11.00 to 16.14) between the rate of complications following primary (n = 443, 8.39%) and revision (n = 22, 11.46%) surgeries. Multivariate analyses showed that patients with Medicare (odds ratio [OR]:1.74, 95% CI: 1.17 to 2.61), Medicaid (OR: 2.13, 95% CI: 1.59 to 2.86), or a malignant neoplasm (OR: 3.10, 95% CI: 1.62 to 5.93) were more likely to have complications. Conclusions The rate of major complications following transsphenoidal pituitary surgery is lower than earlier retrospective reports. The overall complication rate following revision surgery was not significantly different from primary surgery. Insurance status and a diagnosis of a malignant neoplasm were associated with a higher rate of complications. Level of Evidence 2C Laryngoscope, 125:311–317, 2015